2021
DOI: 10.1111/apa.15792
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 pandemic dramatically reduced admissions of children with and without chronic conditions to general paediatric wards

Abstract: Aim We examined the impact of the COVID‐19 pandemic on how many children were admitted to Israel's largest tertiary paediatric hospital and why they were admitted. Methods Israel declared COVID‐19 a national emergency on 19 March 2020. This study examined daily hospital admissions to our three general paediatric wards during the COVID‐19 lockdown period from 20 March to 18 April 2020. These 258 admissions were compared with the 4217 admissions from the period immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
1
22
0
3
Order By: Relevance
“…A possible contributing factor to the decrease in the number of children with KD may be the reduction in the transmission of infectious disease due to COVID-19 restrictions [20]. A significant decrease in hospitalizations due to viral and bacterial infections during the COVID-19 period was observed [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A possible contributing factor to the decrease in the number of children with KD may be the reduction in the transmission of infectious disease due to COVID-19 restrictions [20]. A significant decrease in hospitalizations due to viral and bacterial infections during the COVID-19 period was observed [20].…”
Section: Discussionmentioning
confidence: 99%
“…One study revealed that the COVID-19 pandemic dramatically reduced admissions of children with and without chronic conditions to general pediatric wards [20]. The number of daily hospitalizations declined during the COVID-19 period compared with that of the immediate period before COVID-19 and that of 2018 and 2019 [20]. This indicated a reduction of 59% [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…School closures have been a central part of most countries disease preventive strategies, and hence, it has been associated with mitigation of the COVID-19 disease and the reduction in the spread of communicable diseases in children. 3,4 As the Swedish strategy deviated from most other countries with less strict lockdown restrictions and open preschools and primary schools, it offers a unique opportunity to assess the effect of other behavioural changes as explained in the introduction, including basal hygiene routines, on the transmission of paediatric communicable diseases. We report a dramatic reduction in paediatric emergency visits for two communicable diseases mainly with mainly contact/droplet transmission, which was temporally associated with the recommendations from the Public Health Agency of Sweden on behavioural changes including physical distancing, improved basal hygiene and home quarantine when experiencing symptoms of infection.…”
Section: B R I E F R E P O R T Reduction In Paediatric Emergency Visits During the Covid-19 Pandemic In A Region With Open Preschools Andmentioning
confidence: 99%